Next Door to the Dead : Poems - Driskell, Kathleen Mason (Book collections on Project MUSE., 2015)
When Kathleen Driskell tells her husband that she's gone to visit the neighbors, she means something different than most. The noted poet -- whose last book, Seed across Snow, was twice listed as a national bestseller by the Poetry Foundation -- lives in an old country church just outside Louisville, Kentucky. Next door is an old graveyard that she was told had fallen out of use. In this marvelous new collection, this turns out not to be the case as the poet's fascination with the ""neighbors"" brings the burial ground back to life. Driskell frequently strolls the cemetery grounds, imagining th.